PRESENT-DAY CHARACTERISTICS OF WINTER SNOWINESS CHANGE IN THE EAST EUROPEAN PLAIN - L. M. Kitaev (Лëд и снег)
Character of spatial and long-term variability of snow cover is specified for the period 1966–2006. Long-term decrease of snow storage in November and December and absence of changes in January and March are revealed. The standard deviation for regional spatial distribution changes according to changes of snow storage. Long-term changes of the area with displays of the large snowiness (Sср + δs < Si< Sср + 2δs) and extremely large snowiness (Si>> Sср + 2δs) are estimated. The territories where large and extremely large snowiness are displayed does not exceed 12% from the total area, it is not very perilously for economic activity. Long-term changes of the area with displays by the large and extremely large snowiness correspond to long-term changes of snow storage. The area with simultaneous display of extremely large snowiness, extremely large sums of precipitation and extremely low air temperature is small and does not vary year by year. Hence, concurrence of extreme parameters dispositions also cannot be considered dangerous.